Molecular Docking and ADMET Analysis of Bioactive Compounds from Vitex trifolia as Potential COX-2 Anti-Inflammatory Agents - Hanif Hibatulloh; Zulpakor Oktoba; Atri Sri Ulandari; Muhammad Iqbal; Recky Patala (Tropical Biopharmaca Research Center, IPB University, 2026)
Legundi (Vitex trifolia) has been reported to exhibit anti-inflammatory activity; however, the specific bioactive compounds responsible for this effect remain unclear. This study aimed to evaluate the anti-inflammatory potential of bioactive compounds from V. trifolia against cyclooxygenase-2 (COX-2; PDB ID: 5KIR) using an in silico molecular docking approach, along with the analysis of their pharmacokinetic and toxicity profiles. The results showed that persicogenin exhibited the lowest binding affinity of −9.2 kcal/mol and formed hydrogen bonds with key amino acid residues, namely THR 212, HIS 207, and TYR 385. ADMET prediction results indicated that persicogenin met the drug-likeness criteria for an oral drug candidate, demonstrated good intestinal absorption (HIA: 92.29%), high membrane permeability (Caco-2 permeability > 0.9), low volume of distribution (VDss < 0.45), inhibitory activity against CYP2C19 and CYP3A4, and no hepatotoxic potential. These findings suggest that persicogenin may serve as an anti-inflammatory agent.